Drought‐induced changes in flow regimes lead to long‐term losses in mussel‐provided ecosystem services. Issue 6 (25th February 2015) - Vaughn, Caryn C.; Atkinson, Carla L.; Julian, Jason P.
Abstract Extreme hydro‐meteorological events such as droughts are becoming more frequent, intense, and persistent. This is particularly true in the south central USA, where rapidly growing urban areas are running out of water and human‐engineered water storage and management are leading to broad‐scale changes in flow regimes. The Kiamichi River in southeastern Oklahoma, USA, has high fish and freshwater mussel biodiversity. However, water from this rural river is desired by multiple urban areas and other entities. Freshwater mussels are large, long‐lived filter feeders that provide important ecosystem services. We ask how observed changes in mussel biomass and community composition resulting from drought‐induced changes in flow regimes might lead to changes in river ecosystem services. We sampled mussel communities in this river over a 20‐year period that included two severe droughts. We then used laboratory‐derived physiological rates and river‐wide estimates of species‐specific mussel biomass to estimate three aggregate ecosystem services provided by mussels over this time period: biofiltration, nutrient recycling (nitrogen and phosphorus), and nutrient storage (nitrogen, phosphorus, and carbon). Mussel populations declined over 60%, and declines were directly linked to drought‐induced changes in flow regimes. All ecosystem services declined over time and mirrored biomass losses. Mussel declines were exacerbated by human water management, which has increased the magnitude and frequency of hydrologic drought in downstream reaches of the river. Freshwater mussels are globally imperiled and declining around the world. Summed across multiple streams and rivers, mussel losses similar to those we document here could have considerable consequences for downstream water quality although lost biofiltration and nutrient retention. While we cannot control the frequency and severity of climatological droughts, water releases from reservoirs could be used to augment stream flows and prevent compounded anthropogenic stressors.